Pengaruh Model Pembelajaran PBL (Problem Based Learning) pada Materi Virus dalam Kehidupan Terhadap Berpikir Kritis dan Kerjasama Siswa di SMA Negeri 2 Kota Jambi - Sonia Angellina Saputri; Wilda Syahri; Tedjo Sukmono (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to determine the effect of the Problem Based Learning (PBL) model on the topic of Viruses in Life on students’ critical thinking skills and collaboration at SMA Negeri 2 Kota Jambi. The research employed a quasi-experimental method with a matching-only posttest-only control group design. The population consisted of all tenth-grade students of SMA Negeri 2 Kota Jambi, while the sample included two classes: class X1 as the experimental group taught using the PBL model and class X3 as the control group taught using the Discovery Learning model. Research instruments included an essay test to assess critical thinking skills, as well as questionnaires and observation sheets to measure collaboration using a four-point Likert scale. Data were analyzed using normality and homogeneity tests, followed by hypothesis testing with the Mann–Whitney test. The results indicate that the PBL model has an effect on students’ critical thinking skills and collaboration. In conclusion, the implementation of the Problem Based Learning model is effective in enhancing students’ critical thinking skills and collaboration on the topic of Viruses in Life. Keywords: Collaboration, Critical Thinking, Problem Based Learning, Senior High School, Virus